2024
DOI: 10.9734/ajarr/2024/v18i1596
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of AI Tools: A Multifaceted Evaluation of User Perceptions and Emerging Trend

Yewande Alice Marquis,
Tunbosun Oyewale Oladoyinbo,
Samuel Oladiipo Olabanji
et al.

Abstract: The rapid advancement of artificial intelligence (AI) technologies, epitomized by tools like ChatGPT, Claude, Bard, Copilot, and Copy AI, has significantly reshaped various professional landscapes. This study aimed to assess the impact of these AI tools on professional performance, job dynamics, and societal perceptions. Amidst their benefits in enhancing efficiency and introducing novel capabilities, these tools also pose challenges concerning job displacement, ethical implications, and societal balance. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The evaluation of overall satisfaction and the future outlook towards AI in ENT practice revealed a generally positive sentiment among respondents, indicative of the growing acceptance and optimism towards AI integration in the field. A substantial proportion of respondents expressed satisfaction with AI tools, particularly those with moderate to extensive experience in ENT practice [41]. These findings are consistent with previous research by Ahmad et al [42] and Nasseef et al [43], which demonstrated high levels of satisfaction among healthcare professionals with the use of AI in medical decision-making and patient care [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…The evaluation of overall satisfaction and the future outlook towards AI in ENT practice revealed a generally positive sentiment among respondents, indicative of the growing acceptance and optimism towards AI integration in the field. A substantial proportion of respondents expressed satisfaction with AI tools, particularly those with moderate to extensive experience in ENT practice [41]. These findings are consistent with previous research by Ahmad et al [42] and Nasseef et al [43], which demonstrated high levels of satisfaction among healthcare professionals with the use of AI in medical decision-making and patient care [42,43].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the positive relationship between the implementation of AI-driven strategies for regulatory compliance (coefficient 1.5) and higher levels of compliance underlines the strategic role AI plays in this context. This finding is in line with the broader discussions on the necessity of evolving AI technologies to meet the ever-changing regulatory requirements [28,29]. The integration of AI-driven strategies appears to be a crucial factor in not only meeting but also in staying ahead of regulatory curves.…”
Section: Discussion Of Findingssupporting
confidence: 80%
“…This approach involves processing the minimum amount of data necessary, ensuring a clear processing purpose, being transparent with users, and conducting thorough data protection risk assessments. These steps are crucial in using AI without violating data protection laws [28,29]. Moreso, there are concerns about the broader impacts of these regulations.…”
Section: Ai and Regulatory Compliancementioning
confidence: 99%
“…Although conventional strategies in combating insider threats emphasize the importance of robust access controls, continuous monitoring of user activities, and cultivating a security-aware organizational culture, recent trends and incidents underscore the need for a more nuanced approach [13] [14]. There is an emerging consensus on the importance of behavioral analytics and machine learning techniques in identifying anomalous behavior that may indicate an insider threat, as these technologies complement traditional security measures by providing deeper insights into user behavior, thereby enabling more proactive threat detection and response [15] [16]. Moreover, the role of organizational factors in mitigating insider threats has gained recognition, with factors such as employee satisfaction, transparent communication, and ethical leadership being identified as critical in reducing the likelihood of insider threats [17].…”
Section: Database Security and Insider Threatsmentioning
confidence: 99%